2011
DOI: 10.1158/1535-7163.mct-11-0415
|View full text |Cite
|
Sign up to set email alerts
|

The Bcl-2/Bcl-XL/Bcl-w Inhibitor, Navitoclax, Enhances the Activity of Chemotherapeutic Agents In Vitro and In Vivo

Abstract: The ability of a cancer cell to avoid apoptosis is crucial to tumorigenesis and can also contribute to chemoresistance. The Bcl-2 family of prosurvival proteins (Bcl-2, Bcl-X L , Bcl-w, Mcl-1, and A1) plays a key role in these processes. We previously reported the discovery of ABT-263 (navitoclax), a potent small-molecule inhibitor of Bcl-2, Bcl-X L , and Bcl-w. While navitoclax exhibits single-agent activity in tumors dependent on Bcl-2 or Bcl-X L for survival, the expression of Mcl-1 has been shown to confer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(104 citation statements)
references
References 29 publications
(38 reference statements)
10
93
1
Order By: Relevance
“…However, primary human SCLC xenografts were less responsive, as were other SCLC lines in vitro (16). Recent studies have reported synergy between ABT-737 or its relative ABT-263 and cytotoxic drugs in a variety of tumor xenograft models (47,(49)(50)(51), including melanomas (52,53). The IC 50 values we observed for ABT-737 on NOXAoverexpressing melanoma cells in flat culture were comparable with those reported for ABT-737-sensitive SCLC and lymphoid malignancies (13).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…However, primary human SCLC xenografts were less responsive, as were other SCLC lines in vitro (16). Recent studies have reported synergy between ABT-737 or its relative ABT-263 and cytotoxic drugs in a variety of tumor xenograft models (47,(49)(50)(51), including melanomas (52,53). The IC 50 values we observed for ABT-737 on NOXAoverexpressing melanoma cells in flat culture were comparable with those reported for ABT-737-sensitive SCLC and lymphoid malignancies (13).…”
Section: Discussionsupporting
confidence: 81%
“…A number of other cancer types are sensitive to ABT-737 and there is evidence that its addition to chemotherapy regimens is beneficial (15), particularly in combination with antineoplastic drugs that alter the activity of MCL-1 and NOXA (46,47). Two examples are melphalan and flavopiridol, which are both reported to repress MCL-1, for example, in lung carcinoma and myeloma cells (25,29).…”
Section: Discussionmentioning
confidence: 99%
“…Of these, 14 were classified as having strong synergy (Bliss sum greater than 250). We defined this value empirically, on the basis of data showing good combination effects in xenografts of SK-OV-3 cells (18). The cell lines that had high Bliss scores tended to have lower levels of paclitaxel (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We find that both combinations result in growth inhibition levels that are greater than additive in the majority of cell lines tested. Paclitaxel was the superior combination agent, and more than half of the cell lines exhibited Bliss sums greater than 250, a value empirically determined to translate to in vivo models (18). All of the high synergy cell lines expressed measurable levels of Bcl-x L , whereas some of the low synergy cell lines did not.…”
Section: Discussionmentioning
confidence: 99%
“…Navitoclax has been shown to enhance the activity of chemotherapeutic agents (20)(21)(22)(23)(24). However, studies on its ability to enhance targeted therapy have been limited.…”
Section: Introductionmentioning
confidence: 99%